The Influence of Diabetic Foot Exercise on Sugar Levels In Type 2 Diabetes Mellitus Patients at Tanjung Buntung Public Health Center 2018 - Rizki Sari Utami Muchtar; Indah Triyani Dingin (Universitas Muhammadiyah Mataram, 2018)
Diabetes is a chronic disease that occurs either when the pancreas does not produce insulin or when the body is not effective enough in producing insulin. The International Diabates Federation (IDF) shows that the number of people who suffer diabetes in Indonesia is estimated at 10 million and half seventh rank highest in the world, Indonesia is the 4th country with the highest prevalence of diabetes in the world after India, China and the United States. The phenomenon found in the Tanjung Buntung Public Health Center working area in 2017 was 420 of them, 206 men and 214 people. This study aims to determine the influence of diabetic foot gymnastics on blood sugar levels with the research design using the Quasi experimental method with pretest and posttest without control research method, by sample collection using total sampling the sample of 20 respondents. The statistical test in this study uses the Paired T-Test which is tested first in the Shapiro-Wilk normality test. The results of it study indicate a decrease of 196.85 with a value of ρ-value of 0.000 or > 0.05. obtained a decrease average in blood sugar levels before diabetic foot exercises 239.60 mg / dL with poor criteria and after exercise 196.85 mg / dL with moderate criteria. Therefore it can be concluded that there is the influence of diabetic foot exercise on blood sugar levels in type 2 DM patients. Advice from researchers is expected to always be held diabetic foot exercise ini Tanjung Buntung’s health center to reduce blood sugar levels in patient with type 2 diabetesmellitus